Efficacy and safety of enavogliflozin, a novel SGLT2 inhibitor, in Korean people with type 2 diabetes: A 24‐week, multicentre, randomized, double‐blind, placebo‐controlled, phase III trial - Kwak, Soo Heon; Han, Kyung Ah; Kim, Kyung‐Soo; Yu, Jae Myung; Kim, EunSook; Won, Jong Chul; Kang, Jun Goo; Chung, Choon Hee; Oh, Seungjoon; Choi, Sung Hee; Won, Kyu Chang; Kim, Sin Gon; et al. (Diabetes, obesity & metabolism, 2023)
Aims To evaluate the efficacy and safety of a novel sodium‐glucose cotransporter 2 inhibitor, enavogliflozin 0.3 mg monotherapy, in Korean people with type 2 diabetes mellitus (T2DM) inadequately controlled with diet and exercise. Materials and Methods This study was a randomized, double‐blind, placebo‐controlled trial conducted in 23 hospitals. Individuals with haemoglobin A1c (HbA1c) of 7.0%‐10.0% after at least 8 weeks of diet and exercise modification were randomized to receive enavogliflozin 0.3 mg (n = 83) or placebo (n = 84) for 24 weeks. The primary outcome was a change in HbA1c at week 24 from baseline. Secondary outcomes included the proportion of participants achieving HbA1c <7.0%, change in fasting glucose, body weight and lipid levels. Adverse events were investigated throughout the study. Results At week 24, the placebo‐adjusted mean change in HbA1c from baseline in the enavogliflozin group was −0.99% (95% confidence interval −1.24%, −0.74%). The proportions of patients achieving HbA1c <7.0% (71% vs. 24%) at week 24 was significantly higher in the enavogliflozin group (p < .0001). Placebo‐adjusted mean changes in fasting plasma glucose (−40.1 mg/dl) and body weight (−2.5 kg) at week 24 were statistically significant (p < .0001). In addition, a significant decrease in blood pressure, low‐density lipoprotein cholesterol, triglyceride, and homeostasis model assessment of insulin resistance were observed, along with a significant increase in high‐density lipoprotein cholesterol. No significant increase in treatment‐related adverse events was observed for enavogliflozin. Conclusions Monotherapy with enavogliflozin 0.3 mg improved glycaemic control in people with T2DM. Enavogliflozin therapy also exerted beneficial effects on body weight, blood pressure and lipid profile.